Emerging 2D Semiconducting Materials: Tin Diselenide for Ultrafast Photonics. Issue 5 (9th March 2020) - Liu, Jishu; Li, Xiaohui; Guo, Yixuan; Qyyum, Abdual; Shi, Zhaojiang
Abstract: SnSe2, a novel 2D semiconducting material with good photoelectric properties and tunable bandgaps structure, has been widely studied in high‐performance photodetectors and superconductivity applications, etc. Herein, another excellent property, nonlinear optical absorption, is applied to ultrafast photonics. The measured nonlinear optical absorption curve of SnSe2 with modulation depth of 5.52% is obtained. Q‐switching and mode‐locking in Er‐doped fiber lasers based on SnSe2 is reported. A Q‐switched fiber laser can be obtained with a 0.5‐m‐long gain fiber and a 50:50 optical coupler. With 0.75‐m‐long active fiber and a 40:60 optical coupler, mode locking can be obtained. Furthermore, a third‐order bound‐state soliton pulse with a pulse duration of 882 fs can be achieved. The experimental results show that SnSe2 is an excellent optical saturable absorber for the applications of ultrafast photonics. Abstract : SnSe2 has excellent nonlinear optical characteristics. Pulsed laser can be obtained based on SnSe2 . In addition, two Er‐doped ring fiber lasers, incorporating SnSe2 as saturable absorber (SA) with different losses, are compared. Q‐switched and mode‐locked pulses are obtained, respectively. It is proved that SnSe2 has great application potential in ultrafast photonics.